Use of Ozone for Disinfection of PHARMODUCT® Automatic System for Antineoplastic Compounding - Vito Lovino; Antonio Riglietti; Anna Tolomeo; Giuseppe Capasso; Miriana Di Vittorio; Stefano Brattoli; Giuseppe Tesse; Vincenzo Dimiccoli; Marco Spartà; Luana Perioli (Pharmaceuticals)
Background: The purpose of this work was to demonstrate the ozone efficacy for disinfection of the PHARMODUCT® automatic dispensing system for antineoplastic preparation, as a guarantee of a higher grade of cleanliness. While the use of ozone gas disinfection is almost consolidated in food and water treatment, there is a lack of scientific data in the pharmaceutical field. The scope of this study was to demonstrate the ozone efficacy for disinfection of the PHARMODUCT® automatic dispensing system, before starting the antineoplastic preparation, in order to ensure a high degree of cleanliness and, at the same time, to define a biodecontamination procedure that could also be translatable to other automated compounding systems on the market. Methods: Ozone efficacy was determined by calculating the difference (pre-exposure–post-exposure) in CFU counts on the plate. A group of four different ATCC-selected microbial strains were tested using two distinct cycles. The first one was evaluated with an ozone gas concentration of 40 ppm for 40 min; the second cycle increased the concentration to 60 ppm for the same duration. Results: Results showed that exposure to 40 ppm ozone gas led to a 4-log reduction of all tested ATCC strains. In contrast, exposure to 60 ppm ensured a 6-log reduction. Conclusions: The ozone disinfection process, applied to the PHARMODUCT® system, provides a superior grade of cleanliness compared to the manual disinfection procedure, thus offering insight beyond the current anti-inflammatory and analgesic application of ozone therapy in the medical field.